HEAT EXCHANGE IN THE CHANNEL OF A FLAT SOLAR COLLECTOR - Sharofov, Salokhiddin Sirojidinovich (Educational Research in Universal Sciences, 2023)
The article studies the issue of calculating the efficiency of heat transfer in solar air heaters operating in the condition of free convection. Using the theory of the boundary layer of a heater absorber developing on a vertical surface, it is also possible to use the Reynolds analogy formula obtained for forced convection when flowing around flat surfaces in the case of a laminar regime.